Hyponatremia and its Clinical Outcome Among Patients with Hepatic Encephalopathy Due to Liver Cirrhosis Presenting to ATH Abbottabad - Adnan, Sayad Ahmad, Muhammad Iqbal Qasim, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Hepatic encephalopathy (HE) is a potentially reversible complication of liver cirrhosis causing significant mortality. Hyponatremia in cirrhosis is caused by hampered renal function to eliminate free water that results in water retention disproportionate to sodium retention leading to reduced plasma osmolality and is associated with significant morbidity and mortality. The purpose of study was to determine the frequency of hyponatremia among patients of liver cirrhosis with hepatic encephalopathy. Methods: The design of this study was an observational study design which was hospital-based survey and was conducted on 130 patients of liver cirrhosis. A specialized questionnaire was designed to collect all the study information. All data was analyzed using SPSS Statistics version 24. Chi-square test and Spearman's rank test were employed to correlate hyponatremia with HE and its severity. A p-value of <0.05 was considered statistically significant. Results: Among the patients, 92 (71%) males and 38 (29%) females; the mean age of the patients was 56±11.3 years. Hyponatremia was present in 48 (36.9%) patients. Among these, 25 (52%) were male and 23 (48%) were female; 12 (25%) patients had mild Hyponatremia, 28(58.3%) had moderate, and 8 (16.6%) had severe Hyponatremia. HE was significantly associated with hyponatremia with p value of lea than 0.001. Practical Implication: The benefit of our study was undertaken to determine the frequency of hyponatremia among patients of liver cirrhosis with hepatic encephalopathy to provide evidence for hyponatremia as a prognostic factor in HE so that early detection and management of hyponatremia in such patients will help reduce disease burden and mortality in liver cirrhosis. Conclusion: Patients with lower levels of sodium had higher grades/severity of HE. Significant association of hyponatremia was seen with liver cirrhosis and encephalopathy. Keywords: Abbottabad, Cirrhosis, Hepatic encephalopathy, Hyponatremia, Liver.